Implementasi Nilai-Nilai Moderasi Beragama Bagi Peserta Didik Pada Jenjang Sekolah Dasar Dan Sekolah Menengah Pertama Di Desa Tewang Rangkang Kecamatan Tewang Sangalang Garing Kabupaten Katingan - Wirastiani Binti Yusup; Eka Suriansyah; Kadek Sukiada; Elni Purniatuz Zahroh; Alfian Fauzi; Juhey Riyah; Hermalina Karubaba; Delon Septrianto; Lola Vitaloka; Jose Ernest; Rima Noktayani; Arnus Pransisno; Ni Wayan Sutami; Fathimah Tsabitah Al-Khairiyah (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
The Nusantara Real Work Lecture on Religious Moderation is a priority program of the Indonesian Ministry of Religion focusing on community service through collaboration with Religious Universities in realizing religious moderation at KKN locations. In this case, Tewang Rangkang Village became the selected village by the Ministry of Religion by implementing a competition program, namely the organizer of the Christian Guidance Committee for Religious Moderation to become a Religious Moderation Village. The aim of the NMB KKN is to strengthen the religious values of the Tewang Rangkang Village community through the main and superior work program of group IX of the Nusantara KKN Religious Moderation. The NMB KKN implementation method uses a type of research and service, namely PAR Participatory Action Research or action research involving the community, the Tewang Rangkang Village government and the Elementary School and Junior High School Education sectors in facing the excesses of globalization with a lack of community participation in religious activities and a lack of ability to realize moderation. religious. The results of the NMB KKN for 40 days showed that Tewang Rangkang Village had become a Religious Moderation Village by being able to implement the 4 pillars of religious moderation, namely diversity based on ideology, non-violence, tolerance and accommodating local culture. Based on the main and superior work program of Group IX, there is the principle of sustainable development as one of the elements of PAR. Furthermore, the results of NMB Group IX KKN can have an impact on all parties involved through the socialization of religious moderation at the educational levels of SDN 1 Tewang Rangkang, SDN 2 Tewang Rangkang, SMPN 2 Tewang Sangalang Garing and the output obtained, namely inter-religious religious competitions (Islam, Christianity, Hinduism). so as to create harmony between religious communities which is an embodiment of the values of religious moderation at the KKN location in Tewang Rangkang Village, Tewang Sangalang Garing District, Katingan Regency.